1985
DOI: 10.1200/jco.1985.3.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival in small-cell carcinoma of the lung: a population experience.

Abstract: Small-cell lung carcinoma (SCLC) is a rapidly progressive and fatal disease. Historically, surgical resection or radiotherapy of the primary tumor has done little to prolong survival, although the use of combination chemotherapy is more effective. Reported here is the survival experience of 1,538 incident cases of SCLC identified through the Surveillance, Epidemiology and End Results Program in western Washington State from 1974 to 1982. The survival experience of this population series is similar to that repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(15 citation statements)
references
References 32 publications
2
13
0
Order By: Relevance
“…This paper presents the results of a large population based study in a Health Region of the UK, and has demonstrated the impact of changes in treatment policies, which are not brought out in reports of single or multicentre trials, on account of their selection criteria, relatively small numbers and referral bias (Davis et al, 1985;Carter, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…This paper presents the results of a large population based study in a Health Region of the UK, and has demonstrated the impact of changes in treatment policies, which are not brought out in reports of single or multicentre trials, on account of their selection criteria, relatively small numbers and referral bias (Davis et al, 1985;Carter, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…In most North American series, prognosis is significantly more favourable among women (Davis et al, 1985;Johnson et al, 1988;Spiegelman et al, 1989;Wolf et al, 1991;Chute et al, 1997). Neither in our study nor in a French series of 1280 patients included in four consecutive trials did sex appear as a significant independent factor.…”
Section: Discussionmentioning
confidence: 99%
“…[1,2] The aggressive nature of this variant is evidenced by the fact that the overall 2-year survival rate is 5.9% and the 5-year survival rate, a dismal 2.4%. [3,4] These figures have not changed significantly over the past few decades, in spite of several advances in chemotherapy and radiotherapy. [5] The early identification of simple prognostic factors in such a tumor is important, as it would assist in defining sub-groups for which different treatment modalities could be targeted, for example, a sub-group of patients having no reasonable chance of long term survival could be considered for short-term chemotherapy associated with minimal toxicity or offered palliative care only, whereas patients with better chance of long term survival could be treated more aggressively with curative treatment.…”
mentioning
confidence: 99%